Does the Spatial Layout of a Playground Affect the Play Activities in Young Children? A Pilot Study - Sumiya, Masashi; Nonaka, Tetsushi (Frontiers in Psychology, 2021)
Background: The objective of this study was to describe, through measurement of physical activity and observation of free outdoor play, the relation between children’s free play and the spatial layout of the playground. To accomplish this, we altered the spatial layout of the same playground to see how the layout affects the play activity and the physical activity levels in the same children. Methods: Participants were six young children (four girls and two boys; mean age = 5 years and 1 month, SD = 2.59 months). Participants’ physical activity level and the duration of different types of action that occurred in each area and their transitions were compared before and after the alteration of the play-equipment layout using the data from accelerometers and video recordings. Results: A significant increase in physical activity occurred after the spatial layout alteration, which was related to action differences. Before the alteration, children tended to play in a similar manner for a given play area; however, after the alteration, pronounced inter-individual variation in play activity across children was observed. Conclusions: The present exploratory study found that in free play situations in the outdoor playground, the spatial layout of playground affects the pattern of play activity and the physical activity levels of young children.